The role of discussion sections in research articles: the case of health information-seeking studies - Savolainen, Reijo (Information Research an international electronic journal, 2025)
Introduction. Drawing on the ideas of genre analysis, this article elaborates the role of discussion sections as sites where researchers reflect their contributions to a particular field of study. Method. A sample of 100 discussions sections of research articles examining health information seeking was scrutinized by means of descriptive quantitative analysis. To obtain a quantitative overview, the percentage distribution of the codes assigned to the 14 constituents of discussion sections was calculated. The main emphasis was laid on qualitative content analysis. Analysis. The qualitative analysis focused on the content of diverse constituents of discussion sections, for example, interpreting individual research results and reflecting the theoretical contributions of the study. More specifically, the analysis focused on the variation in the constituents´ content. To achieve this, similarities and differences were identified in the ways in which the authors depicted such content per constituent, for example, while summarizing the key findings and reflecting the empirical contribution. Results. The findings indicate that in discussion sections of research articles on health information-seeking studies, researchers direct their main attention to the interpretation of individual (key) findings. While reflecting their contributions to health-information studies, they also compare their findings in order to identify similarities and differences with prior studies. Moreover, they are active to propose topics for future research. In contrast, researchers in the above domain quite seldom employ analytically demanding strategies by explaining the similarities and differences or reflect the theoretical and methodological implications of their study. Conclusion. Researchers prefer a conservative approach by seeking confirmatory support for their findings, rather than challenging them by presenting contrasting evidence.